Human herpes virus 8 antibodies in HIV-positive patients in Surabaya, Indonesia - Devi Oktafiani; Ni Luh Ayu Megasari; Elsa Fitriana; Nasronudin; Maria Inge Lusida; Soetjipto (MDPI AG, 2020)
Background: Human herpesvirus 8 (HHV-8) infection is etiologically related to Kaposi's sarcoma. Antibodies directed against HHV-8 can be detected in 80%-95% of HIV-seropositive patients with KS. HHV-8 serological tests have been done in several countries in Southeast Asia such as Malaysia, and Thailand however no serological data is available in Indonesia. This study was to examine the presence of HHV-8 antibodies in HIV-positive patients in Surabaya, Indonesia. Material and methods: Ninety-one serum samples were collected from HIV-positive patients in Surabaya, Indonesia. Human immunodeficiency virus-positive serum samples were collected from 10 homosexual men, 25 intravenous drug users (IVDUs) and 56 heterosexuals. Serums were then tested for the presence of HHV-8 antibody by using sandwich ELISA (Abbexa Ltd, Cambridge, UK). Results: The total of 91 HIV-infected were testing with antibodies to HHV-8 using enzyme-linked immunosorbent assay. Antibodies of HHV-8 were detected in 7/91 (7.7%) of the samples. According to a gender, six men (85.7%) and a women (14.3%) were positive of HHV-8 antibodies. No correlation regarding the gender and age from this study. The antibodies of HHV-8 was detected among intravenous drug users (IVDUs) men 5/7 (42.8%) and 2/7 (28.6%) from homosexual and heterosexual, respectively. Conclusion: This study found the presence of HHV-8 antibodies in 7.7% of patients in Surabaya, Indonesia. This finding was higher more than Southeast Asian countries. The patients with a positive result could suggest measures to prevent HHV-8 infection.